Digital Literacy Through Teaching English Tourism Supporting Independent Campus Learning Curriculum in Applied Linguistic Studies - Anggayana, I Wayan Agus (Jurnal Manajemen Pelayanan Hotel, 2024)
The implementation of the Independent Campus Learning Curriculum Merdeka Belajar Kampus Merdeka (MBKM) which was initiated by the Indonesian Ministry of Education, Culture, Research and Technology. This curriculum emphasizes flexibility, independent learning, and the relevance of education to the world of work. Applied Linguistic Studies in English Language and Digital Literacy Teaching, Applied linguistics focuses on the application of linguistic theories and methods to solve practical problems in language teaching. The majority of students feel confident in their ability to use digital technology and English in professional contexts. The industry also recognizes students' readiness to enter the world of work with relevant skills. This research produces recommendations (a) Need more practice writing digital content and professional reports in English. (b) Expansion of technology-based projects to strengthen students' digital literacy. (c) Conducting regular evaluations of the curriculum and teaching methods to ensure their relevance and effectiveness. Keywords: Digital Literacy, MBKM, Applied Linguistic, English Tourism